My little train - Ichikawa, Satomi (New York : Philomel Books, 2010)
A little train goes for a ride, taking all the stuffed animals where they want to go.
003-008
Keywords: Railroad trains -- Fiction; Animals -- Fiction; Toys -- Fiction; Stuffed animals (Toys) -- Fiction; Picture books